Expression and localization of HPG axis-related genes in Carassius auratus with different ploidy - Xu, Xiaowei; Yang, Li; Deng, Xinyi; Xiao, Qingwen; Huang, Xu; Wang, Chongqing; Zhou, Yue; Luo, Xiang; Zhang, Yuxin; Xu, Xidan; Qin, Qinbo; Liu, Shaojun (Frontiers in Endocrinology, 2024)
In the Dongting water system, the Carassius auratus (Crucian carp) complex is characterized by the coexistence of diploid forms (2n=100, 2nCC) and polyploid forms. The diploid (2nCC) and triploid C. auratus (3n=150, 3nCC) had the same fertility levels, reaching sexual maturity at one year. The nucleotide sequence, gene expression, methylation, and immunofluorescence of the gonadotropin releasing hormone 2(Gnrh2), Gonadotropin hormone beta(Gthβ), and Gonadotropin-releasing hormone receptor(Gthr) genes pivotal genes of the hypothalamic-pituitary-gonadal (HPG) axis were analyzed. The analysis results indicated that Gnrh2, follicle-stimulating hormone receptor(fshr), and Lethal hybrid rescue(lhr) genes increased the copy number and distinct structural differentiation in 3nCC compared to that in 2nCC. The transcript levels of HPG axis genes in 3nCC were higher than 2nCC (P<0.05), which could promote the production and secretion of sex steroid hormones conducive to the gonadal development of 3nCC. Meanwhile, the DNA methylation levels in the promoter regions of the HPG axis genes were lower in 3nCC than in 2nCC. These results suggested that methylation of the promoter region had a potential regulatory effect on gene structure and expression after triploidization.Immunofluorescence showed that the localization of the Fshβ, Lhβ, and Fshr genes between 3nCC and 2nCC remained unchanged, ensuring the normal expression of these genes at the corresponding sites after triploidization.Relevant research results provide cell and molecular biology evidence for normal reproductive activities such as gonad development and gamete maturation in triploid C. auratus, and contribute to further understanding of the genetic basis for fertility restoration in triploid C. auratus.